Effectivity and safety of mahkota dewa fruit extract compared to meloxicam (phaleria macrocarpa fructus) on osteoarthritis - Rahmadi, Andri Reza; Dewi, Sumartini; Nawawi, A; Adnyana, I K; Wachjudi, Rachmat Gunadi (Indonesian Rheumatology Association, 2016)
Background: Osteoarthritis (OA) is the most common musculoskeletal disease. World Health Organization (WHO) estimates that 10% of the aged over 60 year population have this disease. The aim of OA treatment is to reduce pain, which is the most OA patients chiefcomplaint. People in Indonesia are very interested in use of herbal therapies from original traditional plant to treat pain now, one of the traditional plants that are known havea benefit is Phaleria macrocarpa or Mahkota Dewa fruit. Phaleria macrocarpa has been shown to decrease the degree of inflammation of OA animal model experiments. In order to know what is the effect of this fruit extract to reduce degrees of pain and change the levels of IL-1, IL-6, TNF-Î± in the blood as the marker of inflammation of patients with knee OA, and what is the effects to liver, kidney and haematology in the Indonesian population hasnot been investigatedÂ Methods: The research method is an experimental study and the research design is PROBE (Prospective Randomized Open End Blinded Evaluation), to evaluate the efficacy of the extract Mahkota Dewa fruit (Phaleria macrocarpa fructus) 330 mg (Super Mahkota POMTR 053 345 491) compared to meloxicam 7.5 mg in patients with knee osteoarthritis. The study population was outpatients with knee OA at Rheumatology Clinic Dr Hasan Sadikin Hospital Bandung. Patients are given Phaleria macrocarpa 330 mg or meloxicam 7.5 mg once a day for 14 days. Observations were made to evaluate the degree of pain as measured by VAS and Lequesne index at day 0, day 14 and measured again at day 28,after they are not taking the extract anymore.Results: Phaleria macrocarpa 330 mg is equal to meloxicam 7.5 mg in reducing the degree of pain as measured by VAS (p=0.78) and the Lequesne index (p=0.51). Our finding, t here is no effect of decreasing the proinflammatory cytokine IL-1 (p=0.72), IL-6(p=0.53) and TNF-Î± (p=0.07) in the blood of both groups. Safety analysis shown that this extract is safe for consumption.Conclusions: Phaleria macrocarpa 330 mg equal to meloxicam 7.5 mg in reducing the degree of pain however there is no effect on reducing proinflammatory cytokines in the blood of OA patients who had received therapy for 14 days in both groups. There is no adverse effects found on hematological, liver function and kidneyÂ function after consumption this plantâs fruit extract.Keywords: osteoarthritis, mahkota dewa, phaleria macrocarpa